2002
DOI: 10.1038/sj.leu.2402642
|View full text |Cite
|
Sign up to set email alerts
|

Angio-immunoblastic T cell lymphoma (AILD-TL) rich in large B cells and associated with Epstein–Barr virus infection. A different subtype of AILD-TL?

Abstract: We studied eight patients with characteristic features of angioimmunoblastic T cell lymphoma (AILD-TL) associated with more than 25% of large B cells. Polymerase chain reaction (PCR) analysis showed a clonal rearrangement of the T cell receptor (TCR)-gamma chain gene in all cases. One additional case showed a clonal rearrangement of the TCR-beta chain gene by Southern blot hybridization. PCR analysis showed a clonal immunoglobulin rearrangement in three cases presenting with more than 50% of large B cells wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 38 publications
(38 reference statements)
4
28
0
2
Order By: Relevance
“…Whether these signals indicate clonal B-cell subpopulations that are also described in healthy individuals 34 or represent true crosslineage rearrangements in the malignant T cells cannot be definitely judged by this analysis alone, although cross-lineage Ig rearrangements would rather result in comparable strong clonal PCR products as generated by TCR PCR. Incidence of Ig clonality was highest in AILT (32%), close to the frequencies identified by Smith et al 28 and Lome-Moldonado et al, 35 but higher than reported by Frizzera. 27 In this entity, Ig clonality most likely corresponds to expanded B-cell clones 28,[35][36][37][38] in line with the occurrence of secondary Epstein-Barr viruspositive B-cell lymphoma after AILT.…”
Section: Anaplastic Large Cell Lymphomasupporting
confidence: 53%
See 1 more Smart Citation
“…Whether these signals indicate clonal B-cell subpopulations that are also described in healthy individuals 34 or represent true crosslineage rearrangements in the malignant T cells cannot be definitely judged by this analysis alone, although cross-lineage Ig rearrangements would rather result in comparable strong clonal PCR products as generated by TCR PCR. Incidence of Ig clonality was highest in AILT (32%), close to the frequencies identified by Smith et al 28 and Lome-Moldonado et al, 35 but higher than reported by Frizzera. 27 In this entity, Ig clonality most likely corresponds to expanded B-cell clones 28,[35][36][37][38] in line with the occurrence of secondary Epstein-Barr viruspositive B-cell lymphoma after AILT.…”
Section: Anaplastic Large Cell Lymphomasupporting
confidence: 53%
“…Incidence of Ig clonality was highest in AILT (32%), close to the frequencies identified by Smith et al 28 and Lome-Moldonado et al, 35 but higher than reported by Frizzera. 27 In this entity, Ig clonality most likely corresponds to expanded B-cell clones 28,[35][36][37][38] in line with the occurrence of secondary Epstein-Barr viruspositive B-cell lymphoma after AILT. 38,39 Also in T-LGL the association with B-cell proliferations is described.…”
Section: Anaplastic Large Cell Lymphomasupporting
confidence: 53%
“…Lome-Maldonado et al 4 have reported in a series of angioimmunoblastic Tcell lymphoma with a large B-cell proliferation that the presence of the large B cells made no significant prognostic impact. In their particular study, they proposed angioimmunoblastic T-cell lymphoma with a large B-cell proliferation as a specific subtype of angioimmunoblastic T-cell lymphoma, so that it would not be mistaken for a T-cell-rich large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…3 Such a proliferation has also been reported in angioimmunoblastic T-cell lymphoma. 4 Recently, expression of CD10 by the neoplastic T cells in angioimmunoblastic T-cell lymphoma was reported. 5 As cases of peripheral T-cell lymphoma, unspecified, failed to show a similar pattern of aberrant CD10 expression, CD10 emerged as a useful tool to help discriminate peripheral T-cell lymphoma from angioimmunoblastic T-cell lymphoma.…”
mentioning
confidence: 99%
“…Clinically, the disease is quite aggressive and can be further complicated by possible transformation of the clonal EBV? B-cells into a diffuse large B-cell lymphoma [40][41][42]. At immunophenotyping, neoplastic cells are CD3?, CD4?, and more often lack one of more T-cell associated antigens such as CD5 and CD7 [43].…”
Section: Molecular Pathology Of Alclmentioning
confidence: 99%